THE USE OF SPEECHRECOGNITION TO FIND OUT READING ERRORS ON GOOGLE TRANSLATE - Aulya Fitrie; Ari Khairurrijal Fahmi (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
This study aims to find out what are the errors in reading 50 Arabic vocabularies using speech recognition found on google translate. This research is descriptive qualitative research, with collection techniques using observation and documentation techniques. Data used in this research is 50 vocabularies prepared for reading by 20 students. Data analysis techniques used in research it is an interactive data analysis. The research result obtained is that several vocabularies that have many errors, in the accuracy of letters, and there is also a vocabulary that has the correct letter and vowel accuracy. Errors found in using speech recognition very diverse, such as the arrangement of letters that do not match up with what is captured by the speech recognition function from google translate. Common reading errors in the vocabulary prepared by the researcher an error in the vocabulary ending in the letter Ta’ Marbutah “ة”. This is due to the arrangement of letters and vowels in the vocabulary prepared by the researcher is not by the result captures by google translate when students read it.